2-10x=(3x-7)(x+1)

Thank you for the opportunity to help you with your question!

first we need to expand the equation on the right

2-10x=(3x(x+1) -7(x+1)

2- 10x= 3x^2 + 3x-7x-7

2-10x= 3x^2 -4x -7

3x^2 -4x + 10x -7 -2 = 0

3x^2 + 6x -9 = 0

3x^2 + 9x-3x -9 =0

3x(x+3) -3(x+3 )=0

(3x-3) (x+3 ) = 0

3x= 3 or x+3 = 0

x= 3/3 or x= -3

x= 1 or -3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up